Robust PID tuning of AVR system based on Indirect Design Approach-2 - Ahmad, Mohd Ashraf; Mohd Tumari, Mohd Zaidi; Ghazali, Mohd Riduwan; Suid, Mohd Helmi; Jui, Julakha Jahan (2023)
The Automatic Voltage Regulator (AVR) has been developed with the automated purpose of maintaining voltage stability for synchronous generators. This structure is